Neurological Soft Signs in the Clinical Course of Schizophrenia: Results of a Meta-Analysis - Bachmann, Silke; Degen, Christina; Geider, Franz Josef; Schröder, Johannes (Frontiers in Psychiatry, 2014)
Neurological soft signs (NSS) comprise subtle deficits in sensory integration, motor coordination, and sequencing of complex motor acts which are typically observed in the majority of schizophrenia patients, including chronic cases and neuroleptic-naïve first-episode patients. However, recent studies clearly demonstrate that NSS are not a static feature of schizophrenia but vary in the clinical course of the disorder. This effect was investigated in a meta-analysis based on 17 longitudinal studies published between 1992 and 2012. Studies included between 10 and 93 patients with schizophrenia spectrum disorders (total number 787) with follow-up periods between 2 and 208 weeks. Beside the Neurological Examination Scale, the Cambridge Neurological Inventory and the Heidelberg NSS Scale were used to assess NSS. All but three studies found NSS to decrease in parallel with remission of psychopathological symptoms. This effect was more pronounced in patients with a remitting compared to a non-remitting, chronic course (Cohen´s d 0.81 vs. 0.15) and was significantly correlated with length of the follow-up period (r=-0.64) but not with age (r=0.28). NSS scores did not decrease to the level typically observed in healthy controls. From a clinical perspective, NSS may therefore be used to identify subjects at risk to develop schizophrenia and to monitor disease progression.